Answer:
B
Step-by-step explanation: 6 21 9 45
49 × 17 + 49 × 3
49 × (17 + 3)
49 × 20
So for eliminating, you only solve for one variable first.
I solved for y, so I multiplied by -4 to eliminate the x.
Then I got y= -1
I then substituted that to one of the equations to get x.
Answer:
p = 2
n = 14
m = 3
Step-by-step explanation:
In order to be able combine (either add or subtract) rational expressions we need to write them with a common (similar) denominator. For that reason we first find the Least Common Denominator of both fractions, that way understanding how to express the two fractions using equivalent fractions with like denominator that can be combined.
We see that the denominator of the first fraction contains the factor "x", therefore "x" has to be a factor of that least common denominator.
We also see that the second fraction contains "2" as a factor, therefore 2 has to be a factor as well for our Least Common Denominator (LCD)
So the LCD we need is the product: 2*x which we write as 2x.
Now we write the first fraction as an equivalent one but with denominator "2x" by multiplying top and bottom by 2 (and thus not changing the actual value of the fraction): ![\frac{7}{x} =\frac{7*2}{x*2} =\frac{14}{2x}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7Bx%7D%20%3D%5Cfrac%7B7%2A2%7D%7Bx%2A2%7D%20%3D%5Cfrac%7B14%7D%7B2x%7D)
Next we do the same with the second fraction, this time multiplying top and bottom by the factor "x":
![\frac{3}{2} =\frac{3x}{2x}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D%20%3D%5Cfrac%7B3x%7D%7B2x%7D)
Now that both fractions are written showing the same denominator , we can combine them as indicated:
![\frac{7}{x} -\frac{3}{2} =\frac{14}{2x} -\frac{3x}{2x} =\frac{14-3x}{2x}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7Bx%7D%20-%5Cfrac%7B3%7D%7B2%7D%20%3D%5Cfrac%7B14%7D%7B2x%7D%20-%5Cfrac%7B3x%7D%7B2x%7D%20%3D%5Cfrac%7B14-3x%7D%7B2x%7D)
This expression gives as then the values for the requested coefficients.
p = 2
n = 14
m = 3
Hello!
![\large\boxed{c = 2}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7Bc%20%3D%202%7D)
8c - 3c + 3 = 13
Begin by combining like terms:
5c + 3 = 13
Subtract 3 from both sides:
5c + 3 - 3 = 13 - 3
5c = 10
Divide both sides by 5:
5c/5 = 10/5
c = 2.
Option D. D has the matrix of constants [[12], [11], [4]].
Step-by-step explanation:
Step 1:
With the given equations, we can form matrices to represent them.
The coefficients of x, y, and z form a matrix of order 3 ×3, the variables x, y, and z form a matrix of order 1 ×3 and the constants form a matrix of order 1 ×3.
Step 2:
The linear system A is represented as
.
Step 3:
The linear system B is represented as
.
Step 4:
The linear system C is represented as
.
Step 5:
The linear system D is represented as
.
Step 6:
Of the four options, the linear system D has the matrix of constants [[12], [11], [4]]. So the answer is option D. D.